Impact of diabetes mellitus on clinical outcomes after heart transplantation. Issue 11 (12th September 2021) - Feng, Kent Y.; Henricksen, Erik J.; Wayda, Brian; Moayedi, Yasbanoo; Lee, Roy; Han, Jiho; Multani, Ashrit; Yang, Wenjia; Purewal, Saira; Puing, Alfredo G.; Basina, Marina; Teuteberg, Jeffrey J.; et al.
Abstract: Purpose: Diabetes mellitus (DM) is common among recipients of heart transplantation (HTx) but its impact on clinical outcomes is unclear. We evaluated the associations between pretransplant DM and posttransplant DM (PTDM) and outcomes among adults receiving HTx at a single center. Methods: We performed a retrospective study (range 01/2008 – 07/2018), n = 244. The primary outcome was survival; secondary outcomes included acute rejection, cardiac allograft vasculopathy, infection requiring hospitalization, macrovascular events, and dialysis initiation post‐transplant. Comparisons were performed using Kaplan‐Meier and multivariable Cox regression analyses. Results: Pretransplant DM was present in 75 (30.7%) patients and was associated with a higher risk for infection requiring hospitalization ( p < 0.05), but not with survival or other outcomes. Among the 144 patients without pretransplant DM surviving to 1 year, 29 (20.1%) were diagnosed with PTDM at the 1‐year follow‐up. After multivariable adjustment, PTDM diagnosis at 1‐year remained associated with worse subsequent survival (hazard ratio 2.72, 95% confidence interval 1.03‐7.16). Predictors of PTDM at 1‐year included cytomegalovirus seropositivity and higher prednisone dose (> 5 mg/day) at 1‐year follow‐up. Conclusions: Compared to HTx recipients without baseline DM, those with baseline DM have a higher risk for infections requiring hospitalization, and those who develop DM after HTx have worse survival.